The impact of the recipient and donor interferon lambda-3 polymorphism on the course of HCV infection following liver transplantation - Wieczorek-Godlewska, Renata (Clin Exp Hepatol, 2017)
AIM OF THE STUDY: Aim of the study was to assess the impact of the recipient and donor interferon lambda-3 (IFNL3) single-nucleotide polymorphisms (SNPs) rs12979860 and rs8099917 on the course of hepatitis C virus (HCV) reinfection following liver transplantation. MATERIAL AND METHODS: The study involved 141 subjects after liver transplantation for HCV-induced cirrhosis, performed between 2000 and 2015. It assessed the impact of both SNPs on the outcomes of interferon/ribavirin (IFN/RBV) treatment following transplantation, HCV viral load, laboratory test results, histological lesions in the liver graft, the risk of acute rejection, and the development of hepatocellular carcinoma (HCC) in patient’s own liver. RESULTS: In the case of rs12979860, SVR was achieved in 58.8% of recipients with the CC genotype, and only 12% of recipients with the TT genotype (p = 0.016). Recipients with the rs12979860 CC variant had lower viral load and lower alanine transaminase (ALT) activity than recipients with a non-CC variant. Opposite effects were demonstrated in the analysis of the donors’ genotype. Recipients with the unfavorable variants (rs12979860 TT and rs8099917 GG) had a lower risk of graft rejection and tended to have a higher risk of developing HCC in their own liver. CONCLUSIONS: The IFNL3 rs12979860 polymorphism may be considered a predictor for IFN/RBV effectiveness following liver transplantation. The course of HCV reinfection following liver transplantation may be more aggressive if an unfavorable variant in the recipient coexists with a promising variant in the donor. Particularly careful monitoring for HCC in recipients with unfavorable IFNL3 variants is warranted.